The Translation Analysis of the Main Character's Exclamatory Sentences from Jenny Han's English Novel "We'll Always Have Summer" to Its Indonesian Version By Chefira Inda P - Thohiriyah, Thohiriyah; Amanda, Tiara Fany (Journal of English Language and Education, 2025)
This study investigates the translation of exclamatory sentences spoken by the main character, Belly Conklin, in Jenny Han’s We’ll Always Have Summer, from English into Indonesian. Recognizing the pivotal role of exclamations in conveying emotions, cultural values, and pragmatic functions in literary works, this research addresses the gap in understanding how these elements are preserved during translation. Employing a qualitative descriptive methodology, the analysis focuses on eleven exclamatory sentences, examining their emotional expressions based on Darwin’s theory (1872) and their cultural and pragmatic meanings through Yule’s pragmatics framework (1996). The findings reveal that most exclamations express joy, followed by anger and sadness, with many containing both cultural and pragmatic meanings. The study underscores the importance of contextual and cultural awareness in translation to accurately convey emotional and social nuances, providing valuable insights for translators and scholars in intercultural literary translation.